Electrochemical precipitation of neptunium with a micro electrochemical quartz crystal microbalance - Medina, Adan Schafer (J Radioanal Nucl Chem, 2020)
Microliter volumes are used in electrochemical detection and preconcentration of radionuclides to reduce the dose received by researchers and equipment. Unfortunately, there is a lack of analysis of radionuclides with coupled electrochemical techniques and microliter volume reactors. The goals of this work are 1) to develop a miniaturized micro-electrochemical quartz crystal microbalance (µeQCM) reactor for use in small volume (50–200 µL) electrogravimetric experiments and 2) to use this reactor to characterize the preconcentration of neptunium on carbon electrodes via electroprecipitation. We successfully deposited neptunium in the new µeQCM reactor and verified its operation. We found that preconcentration of neptunium on carbon coated electrodes was possible by chronoamperometry at −1.6 V(Ag/AgCl). The mass shift of the resulting precipitate was indicative of the amount of neptunium on the electrode, although the correlation between the mass increase and activity of the preconcentrated material was not linear. Neptunium precipitate reduced electron transfer to the solution as evidenced by the increase in charge transfer resistance compared to bare electrodes.